2019
DOI: 10.1002/adtp.201900043
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineering of Mesenchymal Stem Cells via Surface Modification for Efficient Cancer Therapy

Abstract: Mesenchymal stem cells (MSCs) can be used for tumor-specific delivery of small molecular weight anticancer drugs by using nanoparticle-encapsulated forms of the drugs. Current approaches to incorporate nanoparticles in MSCs rely on nonspecific endocytosis of nanoparticles or their conjugation to the cell surface via endogenous amines and thiols. These methods result in sub-optimal drug loading, which hinders the widespread application of MSCs as drug carriers. An advanced nanoengineering strategy is reported h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…MSCs were found to not be sensitive to paclitaxel induced cytotoxicity [45]. In addition, these studies also demonstrated improved tumor growth inhibition in a platinum-sensitive orthotopic ovarian tumor model [22,44]. Tumor xenografts established from immortalized cell lines are easy to develop, reproducible, easy to measure by incorporating bioluminescence, and relatively inexpensive [46].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…MSCs were found to not be sensitive to paclitaxel induced cytotoxicity [45]. In addition, these studies also demonstrated improved tumor growth inhibition in a platinum-sensitive orthotopic ovarian tumor model [22,44]. Tumor xenografts established from immortalized cell lines are easy to develop, reproducible, easy to measure by incorporating bioluminescence, and relatively inexpensive [46].…”
Section: Discussionmentioning
confidence: 96%
“…In our previous studies, we optimized the glycoengineering protocol to achieve high azide expression on MSCs without affecting their viability or tumor homing characteristics [22,44]. MSCs were found to not be sensitive to paclitaxel induced cytotoxicity [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, NPs can be targeted toward tumors by anchoring on stem cells, often via interaction with amine or thiol functional groups of cell surface [77][78][79][80]. Recently, Layek et al reported that the loading efficiency and retention of NPs on cells could be improved by conjugating cyclooctyne-modified NPs with azide-functionalized MSCs to form a stable triazole at ambient conditions [81]. By this method, the content of PTX was~48 pg per cell, much higher than that reported by other techniques (~1-20 pg per cell), while maintaining cell phenotype.…”
Section: Nanoparticles (Nps)-carrying Stem Cellsmentioning
confidence: 99%
“…Layek et al (2016) demonstrated that culturing MSCs in N-azidoacetylmannosamine-tetraacylated supplemented media effectively generated azide-bearing sialic acid on the cell surface without affecting their viability, migration, and differentiation potential. Azide groups on the surface have been used to conjugate dibenzyl cyclooctyne (DBCO)-functionalized, paclitaxel-loaded NPs to MSCs, which allowed for significantly increased NP loading in MSCs (Layek et al, 2019). Incorporation of DBCO-functionalized NPs on MSCs did not affect the viability and migration of MSCs.…”
Section: Engineered Mscs For Tumor-targeted Drug Deliverymentioning
confidence: 99%